Psychometric Validation of the Information Area of Digital Competence in High School Students in Perú - Teresa Fernández-Bringas, Francisco Sandoval-Arteta, Cristóbal Suárez-Guerrero, Giancarlo Ojeda Mercado (Educational Process: International Journal)
Background/purpose – Few psychometric tests have been identified in the literature that analyze digital competencies in school-aged children. The Evaluation Test of Digital Competencies in Compulsory Education Students (ECODIES, Casillas-Martín et al., 2020) is considered one of the most robust for its measurement. The aim of the study was to assess the psychometric validity of the “ECODIES – Area 1: Information” test with high school students from two Peruvian cities in 2021.